UJI EFEK PENYEMBUHAN LUKA KRIM KOMBINASI EKSTRAK DAUN SIRIH HIJAU (Piper betle L.) DAN MINYAK CENGKEH (Syzygium aromaticum L.) KONSENTRASI 5% PADA TIKUS PUTIH JANTAN GALUR WISTAR METODE DRESSING NON-DEBRIDEMENT - Rinaldy, Iqmal Arfan; Andrie, Mohamad; Taurina, Wintari (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2019)
Wounds are damaged structures and normal anatomical functions due to pathological processes that are influenced by internal and external factors. The wound healing process is affected by the onset of infection. Infection can be minimized by providing nutrition and moist environmental conditions (dressing) to restore the continuity of skin anatomy. Non-debridement is carried out aimed at minimizing the wound healing process by external factors, because debridement is the process of removing tissue and foreign objects from the wound to expose healthy tissue beneath it. The aim of this study was to determine the wound healing activity of cream combination of green betel leaf (Piper betle L.) and clove oil (Syzgium aromaticum L.) with a concentration of 5% with various variations in accelerating the wound healing process of stage II rat dressing non-debridement method. Salve preparations were formulated using vaselin flavum and cera flava bases made with three variations of the ratio of active substances, namely F1 (25:75), F2 (50:50) and F3 (75:25). The combination ointment was applied to the wound and quantified by the area of the wound using the Macbiophotonic Image J program to obtain the Area Under Curve (AUC) value and analyzed statistically using SPSS22. The highest average AUC value is, F3 (75:25) of 1108,41% Ã— days. The results of the analysis showed that the group gave significantly different results. The physical test results show that all formulas have good physical properties. Keyword: Test wound healing effect, Piper betle L., Syzygium aromaticum L., Dressing, Non- debridement